2010
DOI: 10.3109/00365590903335221
|View full text |Cite
|
Sign up to set email alerts
|

Long-term treatment and prognostic factors of α1-blockers for lower urinary tract symptoms associated with benign prostatic hyperplasia: A pilot study comparing naftopidil and tamsulosin hydrochloride

Abstract: No significant differences were observed between the drugs for the failure rate. Each treatment had a unique factor for prognosis, such as history of AUR for NAF and complications of OAB for TAM. Therefore, it will be necessary to use the two alpha(1)-blockers properly, considering the patient's background.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 17 publications
0
20
1
Order By: Relevance
“…Although it is known that PVR is not an appropriate objective parameter, because its value fluctuates with each evaluation 23 and baseline PVR has little prognostic value for the risk of BPH-related invasive therapy in patients on a1-blockers and watchful waiting, 24 it is reported that the treatment failure rate was significantly high for patients with PVR Ն30 mL as well as those with a PV Ն35 mL, a history of AUR or complications of overactive bladder symptoms. 14 The present study had several limitations. First, the results for the small number of patients enrolled could not prove even the short-term efficacy of tamsulosin for Qmax and PVR.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Although it is known that PVR is not an appropriate objective parameter, because its value fluctuates with each evaluation 23 and baseline PVR has little prognostic value for the risk of BPH-related invasive therapy in patients on a1-blockers and watchful waiting, 24 it is reported that the treatment failure rate was significantly high for patients with PVR Ն30 mL as well as those with a PV Ն35 mL, a history of AUR or complications of overactive bladder symptoms. 14 The present study had several limitations. First, the results for the small number of patients enrolled could not prove even the short-term efficacy of tamsulosin for Qmax and PVR.…”
Section: Discussionmentioning
confidence: 82%
“…Kawachi et al reported that there was no significant difference in the proportion of self-discontinuation between naftopidil (5/78, 6.4%) and tamsulosin (3/53, 5.7%). 14 In the present study, if a patient did not come to the hospital to receive a prescription, a questionnaire asking the reason for not coming was mailed to him. The most frequent answer was improvement of LUTS, which was found for 16 patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 PV is a risk factor for failure of treatment with a-blockers including naftopidil. 8,16 Thus, the predictive factors for dose increase of naftopidil to 75 mg/day resemble those for progression to operation and urinary retention. In view of these findings, it is thought that the starting dose of naftopidil should be the maximum dose of 75 mg/day for patients with large PV.…”
Section: Discussionmentioning
confidence: 97%
“…[6][7][8] Another feature of naftopidil is its flexible dose that allows the treatment strategy of selecting a dose suited to the patient's condition, severity of symptoms and increasing the dose if the initial dosage is ineffective. 9 Although naftopidil is usually administered at 50 mg/day, 7,10 the efficacy of 75 mg/day administration has been recently reported.…”
Section: Introductionmentioning
confidence: 99%